Dynamic Analysis of RCC Frame Structure Subjected to Blast Loading - Mukesh Kumar; Vinay Kumar Singh Chandrakar; Parbeen Bano (International Journal of Scientific Research in Civil Engineering, 2021)
The number and intensity of terrorist activities have increased our concern towards the safety of our infrastructure. An explosion due to air blast or any other dynamic loading in air generates a pressure bulb, which grow in size at very high rate. The resulting blast wave releases energy over a small duration and in a small volume, thus generates waves of finite amplitude travelling radially in all directions. A six storey RC frame structure with 3.00 m storey height in seismic zone IV has been considered in this present study, effect of charge weights 100 kg, 300 kg and 500 kg has been studied in three phases. The effect of different charge weights 100 kg, 300 kg and 500 kg has been studied for nodal displacements, velocity, acceleration and stress resultants in three Phases – 1, 2 and 3 for standoff distance 30 m, 35 m and 40 m respectively. The structure is modeled and analyzed by using software Staad Pro V8i-2007. The blast parameters are calculated for stand-off distances by adopting wave scaling law given in IS 4991-1968. Comparison of results is made for different parameters such as variation of blast loads, variation of standoff distances. Bending moment, shear force and axial forces in beams and columns are maximum on front face of the structure due to maximum explosive weight and minimum standoff distance ‘Z’. As the weight of explosive (TNT) Increases, bending moment, shear force and axial force in beams and columns, lateral displacement and velocity at different floor levels increases. If standoff distance increases, bending moment, shear force and axial force in beams and columns, lateral displacement and velocity at different floor levels decreases.